Macroeconomic and Political Determinants of Foreign Direct Investment in Indonesia: An Error Correction Model Aproach - Dirham Syafitra; Abd. Rahim; Sri Astuty; Irwandi (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study examines the effects of Gross Domestic Product (GDP), inflation, interest rates, and political stability on Foreign Direct Investment (FDI) in Indonesia over the period 2003 to 2024. The study employs the Error Correction Model (ECM) to distinguish between short-run and long-run relationships. The results indicate that inflation has a positive and significant effect on FDI in the short run, while political stability has a positive and significant effect on FDI in the long run. Meanwhile, GDP and interest rates do not show a statistically significant effect. These findings suggest that political stability and inflation control should be key priorities in efforts to attract foreign investment.